Campur Kode dan ALih Kode pada Komunikasi Sehari-hari Masyarakat di Sekitar Tahura Bengkulu Tengah - Agita Misriani (Institut Agama Islam Negeri Curup, 2019)
Abstract: This study aims to describe mixed code and code transfer communicating in the daily activities of the Lembak people in the Tahura area and the use of the Tahura area.The scope of this research is non formal activities. Partiipants in this study are, Adolescents, adult and parents, with education ranging from those who are not in school, high school and university. Respondents in this study had different jobs ranging from students, housewife, food sellers, and famers. This research refers to the theory put forward by (Chaer and Agustina 1995:4), Appeal (in Suwito, 1983:5), Nababan ( in Chaer and Agustina, 2004:3) about sociolinguistics. The method used is descriptive qualitative method. After conducting research, the authors found data including, the are four languages used by the Lembak people in Tahura Communicate, namely the Lembak language, Bengkulu Malay Language, Rejang language, an javanese. The use of these four languages is in accordance with the context and participants As a result of languages other than Lembak, code and code switching emerged when poeple communicated in their daily activities.Keywords: Mixed Code, Transfer Code